Islamic Education in the Family: Concept, Role, Relationship, and Parenting Style - Abid Nurhuda (CV. Tripe Konsultan, 2023)
Islamic teachings highly regulate education. Even placed the responsibility of parents and families in determining the formation of the personality of the child. So the purpose of this study is to describe Islamic Education in the family. The method used is qualitative with a literature study approach when collecting data, then the contents are analyzed descriptively and the last is concluded. The results of the research show that Islamic education is the main pillar in the family, so in concept parents' lives should be colored with compassion based on the values of the Qur'an, hadith, and ijma' ulama. He also acts as a leader, guide, educator, and coach in the child's personality's moral, mental, social, physical, faith, and worship. So a good relationship between parents and children is needed, starting from when he is in the womb, he is prayed for goodness. He is given a good name when he is born, followed by instilling education in aqidah, worship, and morality. And the last is moderate democratic parenting, so it is neither authoritarian nor permissive.